IMF Staff papers : Volume 37 No. 4. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1990)
The transition strategy from administratively set interest rates to market rates is discussed. Despite worldwide trends toward financial liberalization, few monetary authorities are prepared to accept as reasonable any interest rate level that is market determined. The paper suggests some helpful indicators to assess the adequacy of interest rates and discusses factors that contribute to a smooth liberalization process. The main conclusion is that interest rate liberalization is not synonymous with laissez-faire policies, but requires the replacement of the administratively set interest rates by indirect monetary management techniques that operate through the market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet